Sex- and site-specific, age-related changes in bone density – a Terry collection study - Niina Korpinen; Petteri Oura; Juho-Antti Junno (Homo)
As modern populations are living longer, age-related health issues have become more common. One growing concern is the age-related bone density loss that increases the individual’s risk for fractures, which unfortunately seems to disproportionately afflict women. These fractures are not only detrimental to the individuals’ lives but also come with a great economic burden to the societies. Although age-related bone loss is a normal phenomenon, studies on archaeological individuals have demonstrated that the pattern how this occurs has experienced changes due to our changing lifestyles. Hence, to add to our understanding of secular trends in age-related bone loss, we studied age- and sex-related differences in vertebral and femoral bone densities of a recent past population of late 19th and early 20th century Americans. We used a sample of 114 individuals (55 males, 59 females) from the Robert J. Terry Anatomical Skeletal Collection. Peripheral quantitative computed tomography (pQCT) was used to scan the dry bones. We took one scan from the 4th lumbar vertebra and three scans from the femur. The associations between the age, sex and bone density were analyzed. We were able to detect age-related bone loss in both vertebra and femur. It was observed that men tended to lose more bone density on the vertebra, whereas bone loss in women was more pronounced in the femur. We speculate that differences to modern and earlier archaeological populations are related to the major lifestyle differences between the periods.